Ethically speaking : voice and values in modern Scottish writing - McGonigal, James; Stirling, Kirsten (Scottish cultural review of language and literature, 2006)
As politics and cultures interact within an increasingly diverse Scotland, and differences in values become more evident across generations, the need for clear understanding and cooperation within and between communities becomes a pressing issue. This relates both to local and larger concerns: language, violence, morality, gender and sexuality, education, ethnicity, truth and lies. The chapters gathered here focus on significant Scottish writers of the late twentieth and early twenty first centuries, (Edwin Morgan, A.L. Kennedy, Liz Lochhead, John Burnside, Jackie Kay, Robin Jenkins, Muriel Sp.